Students’ Perceptions of the Urgency of Hajj as the Fifth Pillar of Islam in the Modern Era: A Case Study at Institut Madani Nusantara - Latif (Journal of Innovative and Creativity, 2025)
The study purpose was to explore the perceptions of students at Institut Madani Nusantara regarding the urgency and relevance of Hajj as the fifth pillar of Islam in the modern era. In today’s rapidly changing world, where religious practices often intersect with technology, global mobility, and modern lifestyles, understanding how young Muslim students view the obligation of Hajj is essential. This research aimed to assess their level of awareness, the influencing factors behind their perceptions, and how they interpret the spiritual and social roles of Hajj today. This research employed a qualitative descriptive approach using in-depth interviews and focus group discussions involving 15 students from the Hajj and Umrah Management program. The participants were selected using purposive sampling to ensure relevant academic and spiritual engagement. Data were analyzed using thematic analysis to identify common patterns, insights, and divergent views among the participants. Findings showed that most students perceive Hajj not only as a religious obligation but also as a symbol of spiritual awakening, unity, and submission to God. However, some challenges were identified, including financial limitations, limited understanding of procedures, and the assumption that Hajj is only relevant for older adults. Technological exposure and educational background influenced their awareness and attitudes significantly. The study concludes that while the urgency of Hajj is acknowledged by students, there is a need for more contextualized educational efforts to enhance both spiritual understanding and practical readiness. Integrating experiential learning in manasik training and using digital platforms may increase interest and preparedness among the younger generation.